Pengaruh Edukasi Optimalisasi Penggunaan Pinjaman Online dan Penggunaan Media Digital Terhadap Pengelolaan Modal Pelaku Usaha Mikro, Kecil dan Menengah Desa Sindangjawa - Harry Sulistyowati, Lisa; Suestri, Suestri; Maidah, Liko; Yanti, Lutvi; Nurkomala, Nita (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2022)
Micro, Small and Medium Enterprises often face challenges in managing capital, especially in utilizing digital technology. Many Micro, Small and Medium Enterprises do not understand the optimal way to use online loans, so they have the potential to experience difficulties in improper debt management. This research aims to improve the financial literacy of MSMEs through education on optimizing the use of online loans and the use of digital media for business development, specifically to analyze the effectiveness of participatory educational interventions on MSMEs' understanding of online loans, evaluate behavioral changes in capital management practices, and measure the impact of digital media adoption on business performance. The method used is to hold a Seminar on Optimizing the Use of Online Loans and the Use of Digital Media by providing material on the importance of understanding the various types of legal online loans, the benefits and risks of online loans for Micro, Small and Medium Enterprises, and how to optimize the use of digital media to market products on e-commerce platforms. The results of the seminar showed that Micro, Small and Medium Enterprises experienced an increase in their understanding related to online loans regarding the benefits, risks, and how to choose a safe and legal platform. Conclusion: Educational interventions are effective in improving MSMEs' understanding of the benefits, risks, and criteria for choosing online lending platforms, resulting in better capital management practices.